The relationship of trait mindfulness to physical and psychological health during pregnancy - Serena Mennitto; Blaine Ditto; Deborah Da Costa (Taylor & Francis Group, 2021)
Introduction Research on mindfulness has extended to the prevention of psychopathology and physical conditions during pregnancy. The purpose of this study was to investigate the relationship between trait mindfulness assessed in the first or early second trimester to health outcomes throughout pregnancy. Methods A total of 510 women were recruited at McGill University-affiliated obstetrics clinics (average gestational age: 13.43 weeks, sd = 1.2). The Mindful Awareness and Attention Scale (MAAS) was administered at baseline. At three timepoints during pregnancy, participants completed the Perceived Stress Scale (PSS-10), the Edinburgh Postnatal Depression Scale (EPDS), the Prenatal Distress Questionnaire-revised (PDQR) and a measure of pregnancy symptom intensity and indicated whether they had been diagnosed with gestational diabetes or high blood pressure. Results Higher MAAS scores predicted lower PSS, EPDS and PDQR scores and less severe physical discomforts throughout pregnancy. MAAS scores were a stronger predictor of PSS scores earlier in pregnancy. Logistic regressions found that trait mindfulness did not predict the presence of physical discomforts, diabetes or high blood pressure. Conclusions These results indicate that trait mindfulness is an important predictor of subjective stress, depression, anxiety and the severity of physical discomforts during pregnancy. These findings suggest that interventions earlier in pregnancy may increase the impact of mindfulness on maternal health.